1981
DOI: 10.3133/cir850g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mount St. Helens eruption on selected lakes in Washington

Abstract: On May 18, 1980, after more than a month of earthquakes and eruptions, Mount St. Helens, in southwestern Washington, exploded in a volcanic eruption more violent than any in the conterminous .United States during the 20th century. A lateral blast of hot gas and rock particles devastated an area of about 150 square miles on the northern side of the mountain knocking down trees to a distance of 15 miles. Several minutes later, a giant ash cloud rose to about 60,000 feet. Winds then carried the ash cloud across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 3 publications
2
23
0
Order By: Relevance
“…The severe alterations to the thermal and DO characteristics of Spirit Lake immediately after the eruption are discussed in detail in Dion and Embrey (1981). In May 1981 temperatures within the water column were relatively the same after spring overturn, and DO concentrations near the surface and near the bottom were 5.2 and 3.2 mg/L (milligrams per liter), respectively.…”
Section: Chemical Characteristics Dissolved Oxygenmentioning
confidence: 99%
See 2 more Smart Citations
“…The severe alterations to the thermal and DO characteristics of Spirit Lake immediately after the eruption are discussed in detail in Dion and Embrey (1981). In May 1981 temperatures within the water column were relatively the same after spring overturn, and DO concentrations near the surface and near the bottom were 5.2 and 3.2 mg/L (milligrams per liter), respectively.…”
Section: Chemical Characteristics Dissolved Oxygenmentioning
confidence: 99%
“…Two types of optical conditions were observed that deviated from the clear-blue, preeruption condition in the study lakes: (1) water severely turbid and gray in color from suspended particulate matter, typified by St. Helens and Venus Lakes; and (2) water relatively clear but intensely brown-stained from dissolved organic material, typified by Spirit Lake. Increased concentrations of total and dissolved organic and inorganic chemicals dramatically changed the chemical character of Spirit, Fawn, and Venus Lakes, but essentially did not change the chemistry of Walupt Lake, 37 miles northeast of the volcano (Dion and Embrey, 1981 The posteruption physical, chemical, and biological conditions of Spirit, St. Helens, Venus, and Deadmans Lakes varied according to their distance from the volcano and the initial degree of effect in 1980. Varying conditions from 1980 to 1982 in the lakes were probably due in part to the water-exchange times (time required for the water volume to be replaced by an equal volume of water from inflows) for each lake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the concentration of dissolved organic carbon (DOC) in blast-zone lakes has been discussed by Dion and Embrey (1981), Wissmar, Devol, Nevissi, and Sedell, (1982), Pereira and others (1982), and McKnight and others (1982). During the summer of 1980, DOC concentrations were greatest in South Fork Castle, Coldwater and Spirit Lakes.…”
Section: Organic Constituentsmentioning
confidence: 99%
“…The volume of the lake increased by about 14 times during this interval, which indicates that dissolution of volcanic deposits in the watershed continued to be a source of dissolved inorganic constituents. The changes in the inorganic chemistry of lakes in the second group varied with the position of the lake relative to different blast deposits (Dion and Embrey, 1981;Wissmar, Devol, Nevissi, and Sedell, 1982). Lake, March 28, 1980, andJune 30, 1980 [Date from Dion and Embry.…”
Section: Chemical Characteristics Inorganic Constituentsmentioning
confidence: 99%